ALCOHOL ABUSE FOR LIVER DISEASES - Fauzan Muhamad (JUMP Health (Journal of Ultimate Public Health), 2017)
Alcohols are a rich source of compounds from renewable sources, but they have to be activated in order to allow the modification of their carbon backbone. The latter can be achieved via oxidation to the corresponding aldehydes or ketones. Alcohol dehydrogenases (ADH) are ubiquitous in higher organisms and participate in metabolizing a wide variety of alcohols and aldehydes, as an important “detoxification” mechanism. Alcoholic and alcohol abuse are due to many interconnected factors, including genetics, how you were raised, your social environment, and your emotional health. lower emotional intelligence is predictive of alcohol-related problems.